Religious Aspects Behind the Behaviour of Swearing ‘Anjing’: The Perspective of Indonesia’s Religious Leaders - Anshari, Faridhian; Helencia Putri Permata Sari; Alifian Adrian Marangga (Institut Nalanda, 2025)
Swearing can be seen in the objects chosen for insults, which are often animals. In Indonesia, the term “Anjing” or Dog is frequently used in swearing by both students and the general public. This choice is believed to be influenced by the beliefs of the majority Muslim population, who consider dogs to be impure and forbidden. The goal of this study is to explore the religious aspects of using 'Anjing' as an insult from the perspective of religious leaders in Indonesia. The research aims to show that using “Anjing” as an insult is not only based on Islamic beliefs but is also connected to other religions. This study uses a qualitative approach with document analysis and interviews with five religious’ leaders from different faiths. The findings suggest that in Islam, dogs are not inherently unclean, but their saliva is considered impure. In Christianity, both Catholic and Protestant, 'Dog' has been used historically as an insult by Jews against other religions. In Hinduism, dogs are used in rituals to remove negative energy, and in Buddhism, dogs represent karmic punishment for failed reincarnation. In Confucianism, dogs can be both helpful and harmful, so they are allowed to be eaten. All religions agree that swearing is harmful and has negative effects, both immediately and in the future.